2021
DOI: 10.1111/jocd.13990
|View full text |Cite
|
Sign up to set email alerts
|

The healing effects of facial BOTOX injection on symptoms of depression alongside its effects on beauty preservation

Abstract: form may, in the long run, develop isolation resulting in avoidance of social relationships in individuals and in more severe cases depression and mood disorders. 2,3 Essentially, the reason people go to dermatologists is to improve the beauty and appearance of their face and to achieve a more attractive look with the aim of maintaining and strengthening their position in the family and among their friends as well as in the community. 4 Therefore, the causal relationship between beauty preservation in the face… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 23 publications
0
10
0
3
Order By: Relevance
“…The present experimental animal study is based on two crucial points: the respective results from the literature on the efficiency of anticholinergics on depression [ 153 , 154 , 155 , 156 , 157 , 158 , 159 ] including the results that BoNT-A is effective for the treatment of patients with major depression if injected into the brow muscles [ 258 , 259 , 260 , 261 , 262 , 263 , 264 , 265 , 266 ] and our own previous findings that bilaterally injected intrastriatal BoNT-A reduced anxiety in naïve Wistar rats [ 117 ]. To avoid unwanted side effects of systematically applied classical anticholinergic drugs, and hypothesizing that BoNT-A inhibits the release of ACh also as a local anticholinergic drug, we injected BoNT-A directly into the CPu in hemi-PD rats [ 109 , 110 , 112 , 113 , 114 , 116 , 117 , 118 , 120 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present experimental animal study is based on two crucial points: the respective results from the literature on the efficiency of anticholinergics on depression [ 153 , 154 , 155 , 156 , 157 , 158 , 159 ] including the results that BoNT-A is effective for the treatment of patients with major depression if injected into the brow muscles [ 258 , 259 , 260 , 261 , 262 , 263 , 264 , 265 , 266 ] and our own previous findings that bilaterally injected intrastriatal BoNT-A reduced anxiety in naïve Wistar rats [ 117 ]. To avoid unwanted side effects of systematically applied classical anticholinergic drugs, and hypothesizing that BoNT-A inhibits the release of ACh also as a local anticholinergic drug, we injected BoNT-A directly into the CPu in hemi-PD rats [ 109 , 110 , 112 , 113 , 114 , 116 , 117 , 118 , 120 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, three randomized controlled trials have consistently shown that such effects can be used in the treatment of depression. Mostly female patients suffering from partly chronic and treatment-resistant unipolar depression experienced a quick, strong, and sustained improvement in depressive symptoms after a single glabellar treatment with BoNT-A as a sole or adjunctive therapy [ 258 , 259 , 260 , 262 , 266 , 267 , 270 , 271 , 272 , 273 ]. However, it is still obscure which neurochemical or neuroanatomical pathways this therapeutic approach with BoNT follows.…”
Section: Discussionmentioning
confidence: 99%
“…The mean depression score dropped from 18.9 ± 4.8 to 10.6 ± 2.9 during the follow-up time. The main determinants of improving depression score included young ages, higher educational level, and previous experiences of botulinum toxin use [24].…”
Section: Test Resultsmentioning
confidence: 99%
“…eNOS enzyme incites IL-10 production by producing NO, and induces the HO-1/CO pathway; due to the anti-inflammatory role of this cytokine, it can prevent inflammation. NO-induced HO-1/CO pathway also inhibits signal transmission in the downstream of Toll-like Receptor (TLR), which can also induce an anti-inflammatory effect in ECs [ 38 , 39 ]. Due to the anti-inflammatory role of eNOS enzyme by NO production, the inflammatory process occurs in ECs by suppressing this enzyme; it results in increased permeability of cells, loss of intercellular connections and consequent defects in EC function.…”
Section: The Role Of Exosome In Inflammationmentioning
confidence: 99%